Application of DTM to heat source/sink in squeezing flow of iron oxide polymer nanofluid between electromagnetic surfaces - Reshu Gupta; A.B. Albidah; NFM Noor; Ilyas Khan (Case Studies in Thermal Engineering)
The Riga plates (R.P) generate electromagnetic forces that significantly affect the nanofluid flow. This mechanism, combining both electric and magnetic fields, offers a unique way to control and enhance fluid dynamics, which is not commonly explored in traditional fluid flow models. Therefore, this work studies heat and mass transfer problem for Riga plates with heat sources/sinks and chemical reactions. The nanofluid used in the study consists of iron oxide nanoparticles suspended in a polymer-based fluid. The nanoparticles addition to the base fluid increases the heat transfer rates significantly. The governing partial differential equations (PDEs) for flow, heat, and mass transfer are transformed into nonlinear ordinary differential equations (ODEs) through the appropriate similarity transformation. The differential transform method (DTM) is employed to solve the problem, and the results are compared with numerical methods to ensure accuracy. The study includes graphs illustrating the effects of various physical parameters on velocity, temperature, and concentration. Additionally, tables are provided to examine the behavior of skin friction, the Nusselt number, and the Sherwood number. Key findings include a decrease in temperature with increasing squeezing and radiation parameters, and a reduction in concentration as the Schmidt number and chemical reaction parameter rise.